2011
DOI: 10.1002/ptr.3569
|View full text |Cite
|
Sign up to set email alerts
|

Preventative Effects of 4,4'‐Diphenylmethane‐bis(methyl) Carbamate Isolated from Cortex Mori on Human Umbilical Vein Endothelial Cell Dysfunction Induced by Advanced Glycation End Products

Abstract: Advanced glycation end-products (AGEs) have been regarded as an initial motivating factor in the pathogenesis of endothelial dysfunction in diabetic complications. 4,4'-Diphenylmethane-bis(methyl) carbamate (DMPC), a carbamate compound, was isolated from Cortex Mori and its prevention effects against AGEs-induced endothelial dysfunction were studied. 4,4'-Diphenylmethane-bis(methyl) carbamate significantly reduced cell apoptosis to normal level at 10⁻⁹  mol/L concentration. Advanced glycation end-products up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The growth condition of all the above selected strains were studied in three different medium (BBM, BG-11 and TAP) and the micronutrients necessary for the stimulation of the growth in the media are tabulated. Like other microorganisms, microalgae growth can undergo four growth phases: lag, exponential, stationary, and lysis [13]. The microalgal growth curves obtained in this research illustrate all four characteristic growth phases in a batch culture of microalgae.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…The growth condition of all the above selected strains were studied in three different medium (BBM, BG-11 and TAP) and the micronutrients necessary for the stimulation of the growth in the media are tabulated. Like other microorganisms, microalgae growth can undergo four growth phases: lag, exponential, stationary, and lysis [13]. The microalgal growth curves obtained in this research illustrate all four characteristic growth phases in a batch culture of microalgae.…”
Section: Resultsmentioning
confidence: 63%
“…shows the reaction condition with that of n-hexane to methanol ratio 1:2, solvent dosage 5.0 ml, reaction temperature 90°C, reaction time 2.0 h and catalyst volume 0.5 ml, the conversion yield of the direct transesterification can reach 90.23, 89.25 and 86.65 for Desmodesmus abundans, Desmodesmus armatus and Scendesmus costatogranulatus respectively which produced high lipid content in TAP media. Other reports showed the same conversion yield of 90.02 ± 0.55 wt.% with the reaction condition that n-hexane to 75% ethanol ratio 1:2, solvent dosage 6.0 ml, reaction temperature 90 °C, reaction time 2.0 h and catalyst volume 0.6 ml [13]. Fig-11 shows Conversion yield of methyl esters efficiency among the chosen solvent.…”
Section: Direct-transesterificationmentioning
confidence: 53%
See 1 more Smart Citation
“…A novel compound, 4,4 -diphenylmethane-bis(methyl) carbamate (CM1, also known as DMPC) can prevent AGEs-induced endothelial dysfunction via anti-apoptosis and anti-inflammation on human umbilical vein endothelial cell (HUVEC) [12]. Previously, our results demonstrated that CM1 could attenuate AGEs, HMGB1 and S100B-induced inflammation, apoptosis and oxidative stress response on HUVEC (in press).…”
Section: Introductionmentioning
confidence: 77%
“…It has been shown that CM1 attenuates the intercellular adhesion molecule-1 (ICAM-1) and transforming growth factor-␤1 (TGF-␤1) expressions in HUVEC CM1 also decreased AGEs-induced apoptosis and overexpression of inflammatory cytokines [12]. AGEs exert effects both directly through the formation of protein cross-links that alter the structure and function of extracellular matrix (ECM) and by interacting with specific cell surface receptors [18].…”
Section: Saturated Binding Of Mgh1 and Cm1 To Intact Cellsmentioning
confidence: 98%